Estrategia didáctica “Reo” y su influencia en el aprendizaje del área de ciencia tecnología y ambiente de los estudiantes del 3er grado de la I.E Manuel Fidencio Hidalgo Flores - Castillo Rodriguez, Lorena (2011)
The researeh aimed to determine the influenee of the teaehing strategy "REO" learning area of Seienee Teehnology and Environment of the third grade students of Sehool Manuel Hidalgo Flores Fideneio Nueva Cajamarca Distriet, 201 O. Field data was eolleeted from 33 third grade students of Sehool Manuel Hidalgo Flores Fideneio, who developed a test befare and after attending training sessions to implement the Strategy Teaehing "REO". The eolleeted data were proeessed using the frequeney distribution for the analysis of Jearning in the area of Seienee, Teehnology and Environment, hypothesis testing was performed using the T distribution - Student with 5% signifieance level and degrees of freedom (N-1 ). The implementation of the Strategy Teaehing "REO" improved learning area of . Seienee, Teehnology and Environment of third grade students of Sehool Manuel Hidalgo Flores Fideneio Nueva Cajamarea Distriet, 201 O; with te: 12.48 more TT: 1.67. Consequently, the teaehing strategy "REO" significantly affeets the Jearning area of Seienee, Teehnology and Environment of third grade students of Sehool Manuel Hidalgo Fideneio Flores distriet of Nueva Cajamarea. The results showed that the teaehing strategy "REO" signifieantly affeets the two dimensions of learning area of Seienee, Teehnology and Environment. In understanding the dimension of information, te: tt is greater than 9.44: 1.67. lnquiry and experimentation in te: 11.23 is greater than tt: 1.67.